PID: UMA OPORTUNIDADE DE INCLUSÃO SOCIAL COM A UTILIZAÇÃO DA TECNOLOGIA - Minelli, Leonardo; Padoin, Edson L.; Rohden, Rafael B.; Faccin, Luis F.; Dill, Martin A. A.; Schuch, Regis; Possobom, Camila C.; Sausen, Paulo S.; Dill, Sergio L. (Salão do Conhecimento, 2013)
Resumo